Changes in young adults' mental well-being before and during the early stage of the COVID-19 pandemic: disparities between ethnic groups in Germany - Stephanie Plenty; Chloe Bracegirdle; Jörg Dollmann; Olivia Spiegler (BMC, 2021)
Abstract Background The COVID-19 pandemic resulted in substantial disruptions to the daily lives of young people. Yet knowledge is lacking about changes in mental well-being among young adults, whether those from ethnic minorities were more adversely impacted by the pandemic than the ethnic majority, and the extent to which pandemic-related stressors contributed to any declines in mental well-being. Methods We draw on nationally representative German CILS4COVID data, collected early in the pandemic (N = 3517, Mage = 25). Respondents provided information on mental well-being (psychosomatic complaints, anxiety, depression, life satisfaction) and exposure to pandemic-related stressors (financial worries, health worries, discrimination, contact with COVID-19). Responses on mental well-being were matched to responses from two pre-pandemic waves. Individual fixed effects regressions examined ethnic group differences in changes in mental well-being prior to, and at the early stage of, the pandemic. Path analysis tested the role of pandemic-related stressors in declines in mental well-being. Results Overall, young adults' mental well-being had improved at the pandemic assessment compared to pre-pandemic assessments, and few ethnic group differences in changes were found. However, greater pandemic-related stressors were associated with worsened mental well-being at the pandemic assessment. Among Asian minorities, indirect effects were found on anxiety via health worries, and on depression via health worries and discrimination. For Turkish, Middle Eastern and African minorities, indirect effects on anxiety and depression were found via health worries. Conclusions We did not find widespread declines in mental well-being among young adults at the early stage of the pandemic, and changes in mental well-being prior to and at the early stage of the pandemic were mostly similar across ethnic German and minority groups. Nevertheless, pandemic-related stressors posed risks for young adults' mental well-being, particularly increased discrimination and health worries among Asian minorities, and health worries among Turkish, Middle Eastern and African minorities.